Recent Insights into Anthocyanin Pigmentation, Synthesis, Trafficking, and Regulatory Mechanisms in Rice (Oryza sativa L.) Caryopsis - Enerand Mackon; Guibeline Charlie Jeazet Dongho Epse Mackon; Yafei Ma; Muhammad Haneef Kashif; Niyaz Ali; Babar Usman; Piqing Liu (Biomolecules, 2021)
Anthocyanins are antioxidants used as natural colorants and are beneficial to human health. Anthocyanins contribute to reactive oxygen species detoxification and sustain plant growth and development under different environmental stresses. They are phenolic compounds that are broadly distributed in nature and are responsible for a wide range of attractive coloration in many plant organs. Anthocyanins are found in various parts of plants such as flowers, leaves, stems, shoots, and grains. Considering their nutritional and health attributes, anthocyanin-enriched rice or pigmented rice cultivars are a possible alternative to reduce malnutrition around the globe. Anthocyanin biosynthesis and storage in rice are complex processes in which several structural and regulatory genes are involved. In recent years, significant progress has been achieved in the molecular and genetic mechanism of anthocyanins, and their synthesis is of great interest to researchers and the scientific community. However, limited studies have reported anthocyanin synthesis, transportation, and environmental conditions that can hinder anthocyanin production in rice. Rice is a staple food around the globe, and further research on anthocyanin in rice warrants more attention. In this review, metabolic and pre-biotic activities, the underlying transportation, and storage mechanisms of anthocyanins in rice are discussed in detail. This review provides potential information for the food industry and clues for rice breeding and genetic engineering of rice.